Complacent young citizens or cross-generational solidarity? An analysis of Australian attitudes to democratic politics. Issue 2 (3rd April 2017) - Stoker, Gerry; Li, Jinjing; Halupka, Max; Evans, Mark
ABSTRACT: Negativity towards mainstream politics is at an all-time high, with young people often targeted as the issue. However, are young people really to blame for political malaise? This article seeks to make sense of contemporary debate about political disenchantment in Australia using a cluster analysis to compare levels of complacency across generational cohorts. In this, we find no evidence to support the idea that Australians of any age cohort are complacent about their democracy. Although, there is some evidence of attitudinal differences between cohorts, criticisms of the practice of politics are also widely shared. Moreover, a majority of citizens appear to favour a mix of reforms combining mechanisms to open-up representative politics with opportunities for more direct intervention. To this end, we rebuke the narrative of a specific apathetic or disconnected Australian age cohort.